Repetitive transcranial magnetic stimulation for major depressive disorder: basic principles and future directions - Jean-Philippe Miron; Véronique Desbeaumes Jodoin; Paul Lespérance; Daniel M. Blumberger (SAGE Publishing, 2021)
Repetitive transcranial magnetic stimulation (rTMS) is a safe and well-tolerated intervention for major depressive disorder (MDD). Over 150 randomized controlled trials (RCTs) have been carried out, and its efficacy has been confirmed in dozens of meta-analyses. Real world data has also confirmed the effectiveness of rTMS for MDD in clinical practice, with the most recent literature indicating response rates of 40-50% and remission rates of 25-30%. In this review, we first offer an historical perspective, followed by a review of basic principles, such as putative mechanisms, procedures and protocols, stimulation targets, efficacy and durability of response, side effects, and the placebo controversy. In the second part of this review, we first discuss solutions to increase accessibility to rTMS, such as modifications to treatment equipment, protocols and setting. We continue with possible means to further increase effectiveness, such as treatment personalization and extension. We conclude by addressing the scheduling issue, with accelerated rTMS (arTMS) as a possible solution.